Immunological aspects of endometriosis: review of the literature - L. V. Adamyan; K. N. Arslanyan; O. N. Loginova; L. M. Manukyan; E. I. Kharchenko (Лечащий Врач, 2021)
The review aims to bring together the current understanding regarding the pathogenesis of endometriosis with specific focus on mechanisms behind vascularization of the lesions and the contribution of immune factors in facilitating lesion formation and development. The role of hormones, immune cells, and cytokine signaling is highlighted, in addition to discussing the current pharmaceutical options available for management of pain symptoms in women with endometriosis.